Padrões no uso do espaço arbóreo e terrestre por pequenos mamíferos não voadores em uma área de floresta com araucária do Rio Grande do Sul, Sul do Brasil - Abreu, Maury Sayão Lobato (Universidade do Vale do Rio dos Sinos, 2012)
In this study I investigated patterns in the use of arboreal and terrestrial space by non-volant small mammals on different forest layers in an araucaria forest area (Atlantic Forest domain) in São Francisco de Paula municipality Southern Brazil. The specimens were captured, marked and recaptured during four sampling periods, each one with six nights of sampling, between February and November 2011. The traps were installed on the ground, understory and canopy (50 on each) on a 10x10 grid. The habitat complexity and heterogeneity was determined in each trap stations based on vegetation structure. I estimated the food resource availability (fruits, seeds and invertebrates) for every layer using collect and counting methods, and I also measured 12 microhabitat variables related to vegetation structure. In order to verify association of the complexity and heterogeneity with the diversity and richness of small mammals I used the Pearson linear correlation test. Furthermore, I tested the association hypothesis between species and layers, layer use and food resource availability, and the microhabitat variables and the species abundance. As results, I found eight rodent species and two marsupials during the whole study, with nine species on the ground, seven on the understory, and four on the canopy. Three species was essentially terrestrial (Akodon serrensis, Thaptomys nigrita and Monodelphis dimidiata) and one was essentially arboreal (Juliomys sp.). There was no association of the complexity and heterogeneity to the small mammals richness and diversity (P > 0,1 for all comparisons). However, I detected that the most abundant species showed a preference for some layer, with Akodon montensis, A. serrensis and Delomys dorsalis highly associated with the ground (P < 0,005). The marsupial Gracilinanus microtarsus was the only small mammal species significantly associated to the resource availability on the canopy (P < 0,01). The majority of small mammals was influenced by different microhabitat variables. The absence of correlation of the habitat complexity and heterogeneity with the small mammals’ richness and diversity was possibly due to the spatial and temporal scale used. The results suggested that the frequency of use of layers by small mammals were not strongly influenced by food availability, but probably by other factors like predation risk and competition. The microhabitat preferences of the species were consistent with the vertical layer used, and explained a great part of the space use by small mammals.
Keywords: Complexidade; Disponibilidade de alimento; Estratificação vertical; Heterogeneidade; Marsupiais; Microhabitat; Roedores; Complexity; Food availability; Heterogeneity; Marsupials; Rodents; Vertical stratification; ACCNPQ::Ciências Biológicas::Biologia Geral